Signal interference to electroencephalogram and electrocardiogram signal - Abdul Samad, Noraini (2015)
The increment in a number of electric and electronic devices nowadays ignites the curiosity about the effect of Electromagnetic Interference (EMI) coming from those devices especially in medical environment. In general, the probability for EMI incidents to occur is small. However, the effect from the incident could lead to a very fatal and hazardous side effect. This study strictly focuses on the effect of electromagnetic interference from medical devices that are placed close to the electrocardiogram (ECG) and electroencephalogram (EEG) devices during ECG and EEG signal acquisitions. Since both ECG and EEG machine are most crucial equipments to examine critical part of human body, the devices should be handled with extra precaution towards EMI contamination. An analysis was carried out by using the Fast Fourier Transform (FFT) and QRS Wave Peak Detection to study the effect of EMI from several types of medical devices on both ECG and EEG signals. The result of analysis on the signal exposed to the interference from medical devices was compared to the signal obtained in environment without medical devices.The results showed that interference from blood pressure cuff, electroglotograph, ultrasound, microspirometer and electro muscle stimulator disturbed the quality of signal displayed as well as the amplitude and frequency component of the ECG and EEG signals at 0 cm distance. Even though the EMI can be easily filtered out by using highpass and lowpass filter, the noise can be misinterpreted as a symptom of arrhythmia and consequently leads to unnecessary treatment and panic situation on medical staff.